2017
DOI: 10.1097/md.0000000000006692
|View full text |Cite
|
Sign up to set email alerts
|

Identifying pretreatment baseline factors predictive of distant metastasis in patients with nasopharyngeal carcinoma after radiotherapy

Abstract: This retrospective study was performed to identify pretreatment baseline factors that could predict the development of distant metastasis (DM) in patients with nasopharyngeal carcinoma (NPC).A cohort of 119 NPC patients undergoing radiotherapy (RT) or chemoradiotherapy (CRT) were recruited into the study. Among them, 51 developed DM (DM group) within 3 years after treatment and 68 did not (DM-free group). Various clinicopathological factors were measured before the treatment and analyzed by univariate as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
2
0
1
Order By: Relevance
“…Sementara itu, Wang, dkk. 6 menemukan bahwa titik potong untuk NLR pada KNF adalah 2,6 dan nilai di atas titik potong tersebut bermakna terhadap kejadian metastasis pada KNF. Hingga saat ini, penelitian tentang nilai titik potong NLR pada berbagai kanker, termasuk KNF belum menemukan titik potong yang seragam.…”
Section: Diskusiunclassified
“…Sementara itu, Wang, dkk. 6 menemukan bahwa titik potong untuk NLR pada KNF adalah 2,6 dan nilai di atas titik potong tersebut bermakna terhadap kejadian metastasis pada KNF. Hingga saat ini, penelitian tentang nilai titik potong NLR pada berbagai kanker, termasuk KNF belum menemukan titik potong yang seragam.…”
Section: Diskusiunclassified
“… 5 Previous studies reported that some routine blood parameters, such as the platelet‐ and neutrophil‐lymphocyte ratio (PLR and NLR, respectively) and red blood cell distribution width (RDW), could be used to evaluate the chronic inflammatory state in each patient and predict survival in those with locally advanced NPC (LA‐NPC). 6 , 7 , 8 , 9 , 10 However, studies on the predictive effect of routine blood biomarkers have reported inconsistent results. For example, increased NLR was shown to be a poor independent risk factor in NPC patients, 6 , 7 while other studies found no significant association of this marker with survival.…”
Section: Introductionmentioning
confidence: 99%
“…For example, increased NLR was shown to be a poor independent risk factor in NPC patients, 6 , 7 while other studies found no significant association of this marker with survival. 8 , 9 Inflammation and metabolic status indexes (apolipoprotein‐AI [apoA‐I], high‐density lipoprotein‐cholesterol [HDL‐C]) were shown to be protective risk factors in patients with locally advanced stage III to IV NPC patients. 11 , 12 , 13 ApoA‐I is the core apolipoprotein component in HDL‐C, 14 and HDL‐C/apoA‐I exerts anti‐inflammatory and antithrombotic functions by interacting with routine peripheral blood routine indexes (neutrophil, monocyte, lymphocyte, and platelet).…”
Section: Introductionmentioning
confidence: 99%